Teacher Ethics as a Foundation of Education for Students - Nurcahyani Br Ginting, Indah; Aulia, Nurul (International Journal of Students Education, 2023)
This article discusses the important role of teacher ethics in supporting education which is fundamental for students. Teacher ethics are moral and behavioral principles that must be owned by every teacher in carrying out their duties. Teacher ethics doesn’t just focus on academic aspects, but also involves moral, social, and emotional aspects in interactions with students. Referring to this issue, it means that the most basic lesson or education for students is the ethics of a teacher as the most important lesson that will be a role model or imitated starting from speech, greetings and even punishments and reprimands, all of which. The term ethics comes from the language of philosophy and is even one of its branches. Ethics is also equated with the terms adab, morals, or morals. The study of ethics is a discussion that is close to the teachings of the Islamic religion, because in ethics it is expressed about behavior and attitudes that are good, not good or bad, behavior that has the dimensions of reward and sin, some of the consequences of good and bad or evil behavior according to the guidance of Islamic teachings which are contained in it. norms and provisions are determined